Next Generation Telehealth - Maeder, A.J.; Gogia, S.B.; Hartvigsen, G. (Yearbook of Medical Informatics, 2011)
Telehealth has long been seen as a means of increasing access and quality of care while decreasing costs and logistical burden for remote health care delivery. Underlying technology to support Telehealth has been developed commercially. However, its widespread adoption has been hindered by numerous clinical, social, political, economic and management factors. This paper examines trends which may help to address this situation.First we consider the current status of Telehealth based on some state-of-the-art reviews. Then we present some new future modes of Telehealth services, as described by various prominent authors. From these we identify some common directional themes and fundamental issues affecting the success of future Telehealth innovations.This position paper advances a view that Telehealth in the future will be much more driven by widespread pressure from two different drivers: more ubiquitous connectivity and related technological capabilities due to greater diversity in human communication practices, and new models of care emerging from diverse widespread movements towards health services reform.The IMIA Working Group on Telehealth work agenda will address some specific items within the areas described above.
Keywords: Telehealth; telemedicine; telecare; mhealth; health services